Gluten and FODMAPS-sense of a restriction/when is restriction necessary? - Dieterich, Walburga; Zopf, Yurdagül (Nutrients, 2019)
Gluten-free diet (GFD) is enjoying increasingly popularity, although gluten-free products are considerably more expensive. GFD is absolutely necessary for patients with celiac disease, as in this case even minor amounts of gluten can lead to the destruction of the intestinal mucosa. In addition, GFD is currently the best therapy to improve clinical symptoms of patients with non-celiac gluten sensitivity (NCGS), although the diet may not be as strict as that for patients with celiac disease. Beside gluten, other wheat components such as oligosaccharides and amylase trypsin inhibitors are discussed as triggers of NCGS in this review. An overlap between gastrointestinal symptoms in NCGS and irritable bowel syndrome (IBS) is described. Patients with NCGS attribute their symptoms to the consumption of gluten, while patients with IBS rarely describe gluten as a trigger. Recently, several studies have demonstrated that the introduction of a low FODMAP (fermentable oligo-, di-, monosaccharides, and polyols) diet reduced gastrointestinal symptoms in patients with IBS and this diet is suggested as the first choice of therapy in IBS. However, a low FODMAP diet also eliminates prebiotica and may negatively influence the gut microbiota. For this reason, the diet should be liberalized after symptom improvement. There is no evidence that a GFD is healthier than the standard diet. In contrast, GFD often is accompanied by nutritional deficiencies, mainly minerals and vitamins. Therefore, GFD and low FODMAP diets are not recommended for healthy subjects. Since wheat contains fructans belonging to FODMAPs), a GFD is not only gluten-free but also has less FODMAPs. Thus, symptom improvement cannot be correctly correlated with the reduction of either one or the other.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Celiac disease; Gluten-free diet (GFD); Irritable bowel syndrome (IBS); Low fodmap diet; Non-celiac gluten sensitivity (NCGS)